Quantifying the nitrate levels in bottled water in New Zealand. (23rd December 2021) - Chambers, Tim; Joy, Mike; Wilson, Nick; Hales, Simon; Baker, Michael
Abstract: Objective : There is growing epidemiological evidence linking nitrate contamination to adverse health outcomes. Health concerns may drive consumers towards bottled water, however, nitrate levels in bottled water are not readily available. Methods : We tested water samples from the 10 most popular brands using a TriOS OPUS UV optical nitrate sensor. Results : Overall, all bottled water brands tested returned nitrate levels below 4.4 mg/L NO3. Conclusions : The growing health concerns associated with nitrate contamination suggest that increased reporting of water quality is required. Implications for public health : Mandatory reporting of water quality laboratory reports by bottled water producers would improve transparency to consumers and help public health researchers track potential threats to water quality as new evidence emerges.